Monitoring the end-tidal concentration of sevoflurane for preventing awareness during anesthesia (MEETS-PANDA): A prospective clinical trial. (May 2017) - Wang, Jiebo; Zhang, Liangcheng; Huang, Qijian; Wu, Guohua; Weng, Xianfeng; Lai, Zhongmeng; Lin, Pengtao
Abstract: Objective: It was hypothesized that monitoring end-tidal sevoflurane (ETS) during endoscopic surgery could reduce the incidence of intraoperative awareness in patients undergoing general anesthesia. Herein, the incidence of intraoperative awareness and other correlative factors was recorded and compared. Methods: Two thousand five hundred ASA I–III patients aged 18–80 years who underwent general anesthesia were randomly divided into 2 groups (n = 1250): routine care group (R) and ETS concentration group (E). ETS concentration was monitored in group E and maintained at a sevoflurane minimum alveolar concentration (MAC) of 0.7–1.3; group R was monitored using routine care, and the sevoflurane was maintained. Patients were assessed for intraoperative awareness with a questionnaire on their explicit memory 24–48 h after surgery. Results: A total of 2532 patients were selected, and 86 patients were excluded. As for the groups, 1219 patients were assigned to group E, and 1227 patients were assigned to group R. As for intraoperative awareness, group E had 2 patients, and group R had 14. Compared with group R, the incidence of intraoperative awareness in group E was significantly lower (p = 0.003); the time-averaged ETS concentration and sevoflurane dosage were lower in group E (p < 0.05); and no significant changes were found in tracheal extubation time, intravenous general anesthetic dosage, or postoperative complication incidence in either group (p > 0.05). The incidence of intraoperative awareness was higher in women than men in group R (p < 0.05). Conclusion: Using ETS-guided anesthesia and maintaining the sevoflurane concentration (0.7–1.3 MAC) can decrease the incidence of patient awareness during endoscopic surgery. Highlights: Time-averaged ETS concentration and the dosage of Sevflurane were lower in group E. The incidence of awareness of female was higher than that of male in group R. ETS-guided anesthesia decreases the incidence of awareness of patients.